Union by law : Filipino American labor activists, rights radicalism, and racial capitalism - McCann, Michael W., 1952-; Lovell, George I. (Chicago : The University of Chicago Press, 2020)
Labourers in American West Coast agricultural fields and Alaska salmon canneries found themselves confined to exploitative low-wage jobs in racially segregated workplaces as well as subjected to vigilante violence and other forms of ethnic persecution. In time, though, Filipino workers formed political organisations and affiliated with labour unions to represent their interests and to advance their struggles for class, race, and gender-based social justice. 'Union by Law' analyses the broader social and legal history of Filipino American workers' rights-based struggles, culminating in the devastating landmark Supreme Court ruling, Wards Cove Packing Co. v. Atonio (1989).
Also issued in print: 2020.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on August 12, 2020).
Keywords: Foreign workers, Filipino -- Civil rights -- United States -- History -- 20th century; Filipino Americans -- Political activity; Labor unions -- United States -- History -- 20th century; Race discrimination -- Law and legislation -- United States; Industry; Economics